Geospatial Technique Approach to Land Degradation Assessments in Ghana: The Case of the Ejura Sekyedumase District - Allotey, Albert Nii Moe (Annals of Arid Zone, 2019)
This study examined the use of geographic information systems (GIS) as atool in assessing land degradation caused by water erosion in the Ejura SekyedumaseDistrict, a major food crop production district in Ghana. Data used were land use/cover,slopes/digital elevation models (DEMs) and soil maps. The land use/cover map wasderived from Landsat 7 Enhanced Thematic Mapper Plus (ETM+) 2015 satellite imagery.Digital image processing techniques involving image enhancement, manipulation andclassification were conducted for land use/cover analysis and images were reclassifiedwith an erosion vulnerability map. A slope map (in degrees) was derived from theDEM. The digital soil map, which was classified according to Food and AgricultureOrganization (FAO) groups, was reclassified according to the erodibility classes. Themulti-criteria decision module, with a standardized and weighted linear combinationapproach (WLC) in IDRISI Kilimanjaro was used for the analysis. First, a fuzzy map wascreated for each map layer, which were later combined to produce a land degradationrisk map. The study confirmed that land degradation risks due to erosion exist in thearea. Specifically, the southern and central parts of the district were observed as lowrisk areas (21%), whereas only nine per cent of the area was under high risk. Theseareas were observed in patches around the southeast, southwest and north-central areas.This study demonstrates that remote sensing (RS) is a major environmental data sourcewhich, when integrated with GIS, becomes an effective tool for assessing and mappingland degradation.Key words: Land degradation, Remote Sensing, Geographic Information Systems